Ionic liquids based on DABCO as sustainable green catalysts and solvents: An overview - Sameer Al Ans; Sangita Makone; Abdulfatah Saifan; Priyanka Pinate (Journal of Chemistry Letters)
Significant research interest has been shown in DABCO-based IL catalysts and solvents for improving environmentally friendly catalyst applications in systems. These are seen as promising solvents and catalysts because they have unique physical and chemical properties, such as being cheap, stable at room temperature, not volatile, not toxic, renewable, not flammable, biodegradable, recyclable, and not volatile. However, traditional solvents and catalysts, because of their physical and chemical properties such as volatility, flammability, toxicity, and non-thermal stability, are a hindrance to their applications globally. To overcome these challenges, ionic liquid and DABCO-based IL have been crucial, efficient, and clean ways to improve reaction rates, which reduce the risk of conventional solvents to human health, living organisms, and the environment, as well as to prevent air and water pollution in industry and laboratories. We've talked about the progress made on the DABCO-based ionic liquid catalytic strategy in a systematic and critical way. This includes metal-free ionic liquids, acidic and basic ionic liquids, Lewis acid IL, nanoparticle-supported ionic liquids, polymer ionic liquids, and chiral IL. We did this to learn more about how well DABCO-based IL works to speed up reactions. This review includes an overview of ionic liquids, their types, properties, synthetic methods, characterization, and applications of DABCO-based IL in organic synthesis. We anticipate that this review will offer a more profound understanding of how DABCO-based ionic liquid catalysts and solvents contribute to the development of sustainable, eco-friendly alternatives to high-performance catalysts in the future. We have also outlined the present limitations and potential prospects for DABCO-based ionic liquids. for the development of greener organic synthesis. This review will focus for the first time on the most recent advancements and possible uses of DABCO-based IL as solvents and catalysts in organic synthesis, as documented between 2005 and 2023.